HYDRAULIC TRANSIENT CONTROL OF NEW AND REFURBISHED KAPLAN TURBINE HYDROPOWER SCHEMES IN SLOVENIA - Jernej Mazij; Anton Bergant (Journal of Energy Technology, 2024)
As a natural resource, water is abundant in Slovenia, and its exploitation for electricity generation has a long history. The construction of Kaplan-type turbines is preferred due to topographical and environmental conditions. Water hammer control strategies, including issues of axial hydraulic thrust calculations, are presented in this paper. The case studies include new and refurbished hydropower plants located on all three major river basins in Slovenia.